Comparative and Evolutionary Aspects of Gonadotropin-Inhibitory Hormone and FMRFamide-Like Peptide Systems - Ubuka, Takayoshi; Tsutsui, Kazuyoshi (Frontiers in Neuroscience, 2018)
Gonadotropin-inhibitory hormone (GnIH) is a hypothalamic neuropeptide that was found in the brain of Japanese quail when investigating the existence of RFamide peptides in birds. GnIH was named because it decreased gonadotropin release from cultured anterior pituitary, which was located in the hypothalamo-hypophysial system. GnIH and GnIH precursor gene related peptides have a characteristic C-terminal LPXRFamide (X = L or Q) motif that is conserved in jawed vertebrates. Orthologous peptides to GnIH are also named RFamide related peptide or LPXRFamide peptide from their structure. A G-protein coupled receptor GPR147 is the primary receptor for GnIH. Similarity-based clustering of neuropeptide precursors in metazoan species indicates that GnIH precursor of vertebrates is evolutionarily related to FMRFamide precursor of mollusk and nematode. FMRFamide peptide is the first RFamide peptide that was identified from the ganglia of the venus clam. In order to infer the evolutionary history of the GnIH-GnIH receptor system we investigate the structural similarities between GnIH and its receptor and well-studied nematode Caenorhabditis elegans (C. elegans) FMRFamide-like peptides (FLPs) and their receptors. We also compare the functions of FLPs of nematode with GnIH of chordates. A multiple sequence alignment and phylogenetic analyses of GnIH, neuropeptide FF (NPFF), a paralogous peptide of GnIH, and FLP precursors have shown that GnIH and NPFF precursors belong to different clades and some FLP precursors have structural similarities to either precursor. The peptide coding regions of FLP precursors in the same clade align well with those of GnIH or NPFF precursors. Alignment of GnIH (LPXRFa) peptides of chordates and FLPs of C. elegans grouped the peptides into five groups according to the last C-terminal amino acid sequences, which were MRFa, LRFa, VRFa, IRFa, and PQRFa. Phylogenetic analysis of receptors suggested that GPR147 has evolutionary relationships with FLP receptors, which regulate reproduction, aggression, locomotion, and feeding. GnIH and some FLPs mediate the effect of stress on reproduction and behavior, which may also be a conserved property of these peptide systems. Future studies are needed to investigate the mechanism of how neuropeptide precursor genes are mutated to evolve new neuropeptides and their inheritance.